Optimization of Fermentation Conditions, Enzymatic Properties and Degradation Products of Agarase Produced by Marine Bacterium Sphingomonas sp. Q2 - Xiqian QIAN; Leke QIAO; Hongfeng ZHANG; Xiaolu JIANG; Peng WANG; Jingliang ZHANG (Shipin gongye ke-ji, 2023)
This study was aimed at optimization of the fermentation conditions for agarase production by Sphingomonas sp.Q2 which was isolated from Gracilaria and characterization of its enzymatic properties and degradation products. The optimum fermentation conditions were determined by response surface analysis. The agarase was purified by (NH4)2SO4 precipitation and column separation and its enzymatic properties was investigated. The results indicated that the optimal culture medium components for agarase production were agar 4.42 g/L, K2HPO4 1.30 g/L, NaCl 10.51 g/L. The highest enzyme activity of 1085.71 U/mL was obtained ,which was 1.58 times compared with the initial activity. The crude enzyme was purified 7 times with 112048.82 U/mg of enzyme activity. The recovery rate of agarase was 48.04%. The enzyme had optimal temperature and pH of 40 ℃ and 6.5, respectively. The enzyme activity remained above 90% when stored at the optimum temperature for 8 h. The capital hydrolysates were identified as neoagarotetraose by MS and 13C-NMR. The agarase showed a good thermal stability and high stability, which laid the foundation for the development and application of functional oligosaccharides agar.